2016
DOI: 10.1002/pssb.201600620
|View full text |Cite
|
Sign up to set email alerts
|

First‐principles study of structural, electronic, elastic, and optical properties of cubic KNbO3 and KTaO3 crystals

Abstract: Cubic KNbO3 and KTaO3 crystals are studied using the first‐principles VASP code. By employing local density approximation (LDA), GGA‐PBE, and HSE06, the lattice parameters are optimized and compared with available experimental data, and the best agreement is achieved with HSE06. Electronic structures such as density of states, band structures, and charge‐density distribution are discussed in detail for both crystals. The single‐crystal elastic constants, polycrystalline elastic modulus, compressibility, Poisso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 77 publications
(151 reference statements)
0
10
0
Order By: Relevance
“…In this respect, first-principles density functional theory (DFT) calculations can be useful, which have been extensively applied in studying structural, electronic and optical properties of bulk, surfaces and interfacial structures of KTaO 3 . 41–47 Theoretical results have provided reasonable explanations and reliable predictions on experiments. In this work, we have constructed a NiO/KTaO 3 slab model and performed DFT computations to study the structural details and stability of the interfacial structure, to investigate the electronic and optical properties, to explore the carrier migration at interface, and to reveal the mechanism of the enhancement of photocatalytic activity by loading NiO cocatalyst on KTaO 3 surface.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…In this respect, first-principles density functional theory (DFT) calculations can be useful, which have been extensively applied in studying structural, electronic and optical properties of bulk, surfaces and interfacial structures of KTaO 3 . 41–47 Theoretical results have provided reasonable explanations and reliable predictions on experiments. In this work, we have constructed a NiO/KTaO 3 slab model and performed DFT computations to study the structural details and stability of the interfacial structure, to investigate the electronic and optical properties, to explore the carrier migration at interface, and to reveal the mechanism of the enhancement of photocatalytic activity by loading NiO cocatalyst on KTaO 3 surface.…”
Section: Introductionmentioning
confidence: 72%
“…Further investigations on each component suggest that the VBM and CBM of KTaO 3 slab in the interface are mostly comprised of O 2p states and Ta 5d states, respectively, which are similar with those in bulk. 41 As to NiO side in the interface, the VBM is primarily characterized by the mixture of Ni 3d and O 2p states, while the CBM dominantly comes from Ni 3d states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen, the K atom is at the origin, Ta is in the center and the three oxygen atoms are in the center of three different faces. [53] Hexagonal and tetragonal LiTaO 3 structures, respectively, are shown in Figure 3b and 3c. It should be noted that in several studies it has been reported that LiTaO 3 belongs to the R3c crystallographic group of hexagonal classification, [54] even when there are reports of tetragonal structure [55] (see LiTaO 3 bulk structure of Supplementary Material).…”
Section: Ktao 3 and Litao 3 Bulk Structuresmentioning
confidence: 96%
“…Firstly, simulations are performed on a perfect (i.e., defect-free) crystal structure, but (in reality) defects occur in KSN ceramics. 24,25 Secondly, actual KSN ceramics are polycrystalline materials and grain boundaries have an influence on the experimental results (see Figure 8). The effect of the boundaries is neglected in the simulations.…”
Section: Relation Between Experimentally Determined and Simulation-mentioning
confidence: 99%